Ensino de geografia, desafios e sugestões para a prática educativa escolar - Vale, José Misael Ferreira do [UNESP]; Magnoni, Maria da Graça Mello [UNESP] (My University, 2012)
The text proposes, from the methodological approaches of Paulo Freire, Celestin Freinet and Dermeval Saviani, the development of a geography dialectically conceived, contextualized.

O texto propõe, a partir das propostas metodológicas de Paulo Freire, Célestin Freinet e Dermeval Saviani, o desenvolvimento de uma Geografia dialeticamente pensada, contextualizada.
Teaching geography, challenges and suggestions for educational practice school
Keywords: Teaching geography; Pedagogy of common sense; Dialogic pedagogy and critical pedagogy history; Ensino de geografia; Pedagogia do bom senso; Pedagogia dialógica e pedagogia histórico crítica